Research on Online Calibration Technology of Wideband Radar Target Simulation System - Wu Haosheng, Pan Minghai, Hu Haipeng (Editorial Office of Aero Weaponry, 2021)
Aiming at the problem of amplitude and phase distortion of echo signal generated by wideband radar target simulation system, this paper estimates the amplitude and phase characteristics of the system by online extraction of amplitude and phase error, and the method of joint calibration with active equalizer and FIR filter is used to calibrate the amplitude and phase distortion of echo signal. The active equalizer is used to calibrate the insertion loss which varies with the frequency to avoid the deterioration of the signal dynamic range during the calibration. The amplitude distortion of nonlinear high-frequency oscillation and phase distortion are calibrated by FIR filter which is designed by using chaos particle swarm optimization algorithm. After joint calibration, the amplitude fluctuation of the output signal of the wideband radar target simulation system is less than 1.3 dB, and the group delay fluctuation is less than 2 ns. The amplitude and phase characteristics of the system have been greatly improved, and the dynamic range of echo signal has no obvious deterioration. Therefore, this joint calibration method can be applied to the calibration of wideband radar target simulation system.